Association between early spontaneous abortion and homocysteine metabolism - Lei, Fangliang; Zhang, Lili; Wang, Li; Wu, Wentao; Wang, Fei (Frontiers in Medicine, 2024)
The purpose of this study is to explore the effects of homocysteine (HCY) metabolism and related factors on early spontaneous abortion. Methods: We conducted a hospital-based case-control study and included a total of 500 cases and 1000 controls in Shaanxi China. Pregnant women waiting for delivery in the hospital were interviewed to report their characteristics and other relevant information during pregnancy. The unconditional Logisitic regression model was applied to assess the association between early spontaneous abortion and HCY metabolism and related factors. The multiplicative model was applied to assess the effects of interaction of plasma HCY and serum folate deficiency in early pregnancy, and there was an interaction between serum folate deficiency in early pregnancy and maternal MTHFR 677TT genotype. The direction of the above interactions was all positive, which showed the synergistic effect. The occurrence risk of early spontaneous abortion was significantly increased if multiple factors existed at the same time.